In silico analysis of Pap31 from Bartonella bacilliformis and other Bartonella spp. - Ruiz, Joaquim (2020)
Pap31 is an outer membrane protein of Bartonella bacilliformis which is considered to be a potential antigenic candidate for the development of diagnostic tools. The present study aimed to compare Pap31 from B. bacilliformis with that of other Bartonella spp. The results showed the presence of at least 5 different B. bacilliformis Pap31 alleles, with the strain Ver097 being the most divergent (89.7% of identity with the reference strain KC583). The most significant finding was the presence of a variable number (1 to 3) of 6 amino acid tandem repeats (GTEGGG) in the different B. bacilliformis Pap31 alleles, with no similar structure in other established Bartonella spp., except for Bartonella ancashensis, another Bartonella spp. isolated from chronic cases of Carrion's disease. In both B. bacilliformis and B. ancashensis this repetitive region was coincident with the most predicted immunogenic region of the protein. In other microorganisms, the presence of amino acid tandem repeats has been related to the development of poorly functional antibodies. The findings of this study also suggest a utility of Pap31 amino acid tandem repeats as potential contributors to the immune evasion of Carrion's disease-related Bartonella spp. and the establishment of asymptomatic B. bacilliformis / B. ancashensis infections.